Effects of flux composition on melting behaviour of magnesium AZ91D alloys cast by investment casting in-situ melting technique - Rasoul Sadeghi, 1983-; Mohd. Hasbullah Idris, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Thesis (Sarjana Kejuruteraan (Mekanikal - Teknologi Pembuatan Termaju)) - Universiti Teknologi Malaysia, 2011